Effektifitas Pemberian Pupuk Organik Kambing dan POC Nasa Terhadap Tanaman Pakcoy (Brassica Rapa L.) - Sutrisno Sidabutar; Nikmah Nikmah; Linda Bachrun (Fakultas Pertanian Universitas Borobudur, 2024)
The research was conducted to determine the effectiveness of applying goat organic fertilizer and NASA POC to pakcoy plants that have been carried out in the experimental garden of the faculty of agriculture, Borobudur university which began in May to July 2023. This study used factorial randomized group design (RAK) with two factors and repeated 3 times. The first factor is manure (K) at the level of 100 g, 150g, and 200g. The second factor is NASA POC (P) at the level of 5 ml / l, 6 ml / l, and 7 ml / l. The data were analyzed using the F test and the F test. Data were analyzed using F test and stepwise further test with four (4) testing parameters: Plant height, number of leaves, plant weight, and root length. The results of the study were analyzed using SPSS Version 24 with the conclusion that the interaction between goat manure and (POC) Nasa had no significant effect on plant height, number of leaves, wet weight and root length. Goat manure had a significant effect at the age of 2, 3, 4, and 5 weeks after planting on plant height and number of leaves as well as on wet weight parameters and root length which showed a significant difference at the age of 5 weeks after planting. The best treatment was shown at a dose of 200 g (K3). POC Nasa had a significant effect at the age of 3, 4, and 5 weeks after planting on plant height and number of leaves with the best treatment results at a dose of POC Nasa 5 ml/l (P3)